The genome sequence of the Small Scabious Mining Bee, Andrena marginata Fabricius, 1776 [version 1; peer review: 2 approved] - Joseph Monks; Ryan Mitchell (Wellcome Open Research, 2024)
We present a genome assembly from an individual female Andrena marginata (the Small Scabious Mining Bee; Arthropoda; Insecta; Hymenoptera; Andrenidae). The genome sequence spans 373.60 megabases. Most of the assembly is scaffolded into 6 chromosomal pseudomolecules. The mitochondrial genome has also been assembled and is 21.16 kilobases in length.